Fusion, Gemination or a Morphological Variation? A Case Report on a Diagnostically Challenging Mandibular Molar - Argyro Kavadella; Ioannis Papavasileiou; Maria-Areti Salamouri; Ioannis Papavasileiou; Elpida-Niki Emmanouil-Nikoloussi (Oral, 2025)
Background/Objectives: Dental anomalies can manifest as a consequence of developmental defects and/or genetic influences, which disrupt the normal functioning of the oral cavity and present in various forms. Cases of fusion, gemination and concrescence are rare dental anomalies which are seen in the area of the mandibular molars. Case report: This case report concerns a 69-year-old Greek male patient who presented in the dental office asking for comprehensive oral treatment. During the clinical examination, a morphologically atypical molar was identified in the area of #37–38 presented with a large crown in the mesio-distal dimension (‘double’ crown). Panoramic and periapical radiographs offered valuable insights on the morphology of the irregular tooth, as they revealed the crown and root morphology, including the two pulp chambers and the three parallel roots of the tooth. Discussion: A plausible hypothesis identifies the atypical tooth as a third molar exhibiting morphological variation, a common characteristic of third molars. Additional diagnostic considerations—while supposing the existence of a supernumerary fourth molar—include the developmental anomalies of gemination, concrescence and fusion, as the clinical and radiographic features of the tooth display elements associated with all three. Conclusions: Considering the patient’s history, clinical and radiographic findings and the relevant literature, fusion is determined to be the most probable diagnosis. Early identification of the atypical tooth is essential to facilitate the implementation of appropriate preventive measures and to support informed treatment planning, should invasive procedures such as endodontic or surgical intervention be required in the future.